THE EFFECT OF INFLATION LEVEL, EXCHANGE RATE (EXCHANGE RATE) AND INTEREST RATE LEVEL ON THE COMPOSITE STOCK PRICE INDEX ON THE CAPITAL MARKET AT THE INDONESIA STOCK EXCHANGE, SOUTH KALIMANTAN REPRESENTATIVE OFFICE - Muhammad Zaini; Rosadiro Cahyono (Sean Institute, 2021)
This study aims to determine the extent of the influence on inflation, exchange rates (exchange rates) and interest rates on the stock price index on the IDX and the steps to analyze in decision making, especially for economic and business policies. The number of samples used in this study were 26 sub-sector manufacturing companies listed on the Indonesian Stock Exchange (IDX). The statistical method used in this research is multiple linear regression analysis and the hypothesis test is the F test, T test, and the coefficient of determination. (H3) that competence has the most dominant effect on employee performance.